Pengaruh Fear Of Missing Out (Fomo), Motivasi Hedonis, Dan Suasana Toko Terhadap Pembelian Impulsif Pada Konsumen Coffee Shop: (Survei pada Mahasiswa Generasi Z di Kota Surakarta) - Sera Triya Meilida; Mutya Paramita Pratita (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study was conducted on Generasi Z college students in Surakarta City who had previously purchased at coffee shops. The purpose of this study was to analyze the significant influence of Fear of Missing Out (FoMO), Hedonic Motivation, and Store Atmosphere on Impulsive Buying in coffee shops in Surakarta City. The data used was quantitative. The data source used in this study was primary data. The data analysis techniques used in this study were multiple linear regression analysis, classical assumption test, t-test, F-test, and coefficient of determination (R2) using SPSS. The results of the multiple linear regression analysis of this study were Y = 2.832 + 0.092 X1 + 0.021 X2 + 0.276 X3 + e. The t-test results indicated that the variables Fear of Missing Out (FoMO) and Hedonic Motivation had a positive but insignificant effect on impulsive buying among coffee shop consumers in Surakarta City. Meanwhile, the variable Store Atmosphere had a positive and significant effect on impulsive buying among coffee shop consumers in Surakarta City. The results of the F test show that the model is appropriate in predicting the influence of Fear of Missing Out (FoMO), Hedonic Motivation, and Store Atmosphere on Impulsive Purchases in coffee shop consumers in Surakarta City. The results obtained from the coefficient of determination (R2) are 0.240, meaning that the contribution of the independent influence of X1 (Fear of Missing Out), X2 (Hedonic Motivation), and X3 (Store Atmosphere) on Y (Impulsive Purchases) is 24%. The remaining (100%-24%) = 76% is explained by other variables not included in this study.